Right-sided laryngeal hemiplegia and Horner's syndrome in a horse - Palumbo, M. I. P. [UNESP]; Moreira, J. J. [UNESP]; Olivo, G. [UNESP]; Neto, C. R. [UNESP]; Pyles, M. D. [UNESP]; Watanabe, Marcos Jun [UNESP]; Borges, Alexandre Secorun [UNESP] (Wiley-Blackwell, 2011)
This study describes right laryngeal hemiplegia (LH) and right-sided Horner's syndrome (HS) in a horse. The average temperature of the face was 3.5 degrees C higher on the right compared with the left side, as determined by thermographic imaging. The syndrome occurred following an episode of right mid-cervical cellulitis due to inadvertent perijugular deposition of gentamicin.
Keywords: horse; ptosis; Horner's syndrome; sweating; thermography